Penerapan Sistem Informasi SAK EMKM Melalui Aplikasi Berbasis Android LAMIKRO Pada UMKM Bagus Batu Bata - Yuniartini, Ni Made Yani; Sinarwati, Ni Kadek (Universitas Pendidikan Ganesha, 2022)
This research aims to determine the application of an information system of financial accounting standards for micro, small, and medium entities through the android-based application LAMIKRO on micro, small, and medium sized enterprises in Bagus Batu Bata. This study uses a qualitative method with a descriptive approach. Sources of data in this study are primary data and secondary data. The data obtained were then analyzed by data analysis techniques, namely data collection, data reduction, data presentation, and concluding. The results of this study state that (1) the obstacles experienced by Bagus Batu Bata are the absence of competent Human Resources (HR) in the field of accounting, lack of knowledge of micro, small, and medium enterprises in accounting, micro, small and medium enterprises consider financial reports are not important, micro, small and medium enterprises are still technologically savvy (untechnical), difficulties in separating personal finance and business finance, (2) financial records are still very simple, namely only recording cash in and cash out. Therefore, researchers contribute to assisting in the preparation of financial accounting standards for micro, small, and medium entities, (3) the expected implication is that the LAMIKRO application makes it easier for Bagus Batu Bata's business to compile simple financial reports and can understand accounting in more depth.